Transforming Islamic Religious Education through Nusantara Philosophy: Integrating Popular Pedagogy and Transformative Tauhid - Adona, Putri; Ahida, Ridha (Sekolah Tinggi Ilmu Tarbiyah (STIT) Ahlussunnah Bukittinggi, 2025)
Islamic education in Indonesia faces fundamental challenges in the contemporary era, particularly criticism that the dominant curriculum is normative and doctrinal in nature, failing to balance cognitive aspects with affective and social aspects. Manifestations of this failure include a crisis of character, a decline in the ethos of mutual cooperation, and continuing social inequality. The renewal of Islamic Religious Education must have a strong and contextual philosophical foundation, which in the Indonesian context is offered by Nusantara Philosophy. Nusantara Philosophy, as a post-colonial project that reflects subaltern identity, demands that Islamic Religious Education serve the interests of the oppressed and reject the dualism of theory and practice. This study proposes the integration of Tan Malaka's People's Pedagogy, which has historically proven to be emancipatory, as the operational methodological framework of Nusantara Philosophy. Tan Malaka's People's Pedagogy, although based on Anti-Mystification Materialism, is strongly rooted in Islam as an anti-caste and anti-oppression movement. Its main objectives are liberation from ignorance and oppression, and the formation of agents of social change (Kaum Kromo) through an emphasis on practical skills and collectivity. The key synthesis of the integration of Tan Malaka's People's Pedagogy with the principle of Tawhid (Oneness) results in Transformative Islamic Religious Education, which operationalises Nusantara Philosophy. Transformative Islamic Religious Education emphasises the dialogical and problem-posing methods characteristic of critical pedagogy, as well as the reform of evaluation towards measuring social benefit. This study uses Systematic Literature Review (SLR) to analyse literature, resulting in the formulation of a Transformative Islamic Religious Education model that transforms the role of Islamic Religious Education teachers into emancipatory facilitators, demands curriculum harmonisation, and positions evaluation on the process and social impact, so that Islamic Religious Education becomes a true instrument for social emancipation and the achievement of national dignity.